PENGARUH TEKANAN KOMPETISI TERHADAP KREATIVITAS INOVASIDAN KEUNGGULAN BERSAING UKM BATIK DI KOTA PEKALONGAN - Meutia . (Jurnal Manajemen., 2015)
The governments policy to open up global markets will affect the level of competition is going to SMEs. One industry that is affected is the batik industry in Pekalongan. Government policies to free markets will increase competitive pressures that occur in the market. SMEs indusrtri batik is one that will have an impact of this policy. The purpose of this study was to examine how the effect of competitive pressure on the creativity and innovation of SMEs competitive advantage batik in Pekalongan Central Java Province. Intense competition encourages employers continue to innovate both product innovation, design, staining methods, technology and service innovations in the batik industry that are interested and able to compete both local and export markets. Location of the research done on the SME industry in Pekalongan batik. The sampling technique is purposive sampling on the owner or manager of the batik industry with the manager or owner minimal criteria already in the batik industry at least 5 years. Analyzed using Structural Equation Modeling (SEM) with AMOS 16.0. The results of the study hypothesis of competition pressure allegedly positive effect on the ability of employers put through the creativity of product innovation, the pressure of competition and product innovation creativity alleged significant effect on the competitive advantage of SMEs batik industry. Market forces and the encouragement of entrepreneurs make entrepreneurs constantly have to innovate products to achieve competitive advantage of SMEs. Results of this study are expected to contribute to the theory of Resource Based view (RBV) which confirms that a company trying to maintain a competitive advantage through product innovation. Competitive pressures will encourage employers to creativity innovation so as to have a quality product and varies according to the wishes of consumers.